Pt and Pt-Pd cluster interaction with graphene and TiO₂ based supports: A DFT study - Matsutsu, Molefi (Centre for Catalysis Research, 2017)
Density functional theory (DFT) calculations have been performed to gain insight into the role of defects present on the surface of graphene and TiO₂ based supports on supported metal clusters. The clusters considered are a Pt₃₈ cluster and a bimetallic Pt₃₂Pd₆ alloy. The defects considered on graphene based supports are monovacancy defective graphene, OH and COOH functionalised graphene. The defects considered on TiO₂ based supports are a partially reduced TiO₂(110) surface with a surface oxygen bridge vacancy and hydroxylated TiO₂(110) surface with surface OH groups. The defect free graphene and TiO₂ surfaces were also considered. For both the Pt₃₈ and Pt₃₂Pd₆ cluster, and on both defect containing graphene and TiO₂ (except on hydroxylated TiO₂(110) surface) the binding of the clusters is enhanced relative to binding on the defect free supports. Enhanced binding at the defects imply that the clusters are bound strongly to the support and thus less likely to detach from the support material relative to binding on the defect free supports. Therefore, the defects may improve the durability of the catalyst by limiting particle detachment. The electronic properties of the cluster are modified differently depending on the identity of the defect present on the support. On the graphene based supports, OH functionalisation is expected to result in weaker binding energy of adsorbate molecules, whereas COOH functionalisation is expected to result in stronger binding energy of adsorbates for the supported Pt₃₈ cluster. This is due to different shifts in d-band centre of the facets on the cluster supported on these supports. Therefore, it can be expected that the Pt₃₈ cluster supported on OH functionalised graphene will be more tolerant to poison molecules. This is due to reduced binding strength of adsorbates on OH functionalised graphene compared to adsorption on COOH functionalised graphene. For the Pt₃₂Pd₆ cluster the OH and COOH functional groups do not appreciably modify the d-band centre of the facets available to reactants, and thus is expected not to significantly modify the binding strength of adsorbate molecules relative to binding on the free unsupported Pt₃₂Pd₆ cluster. The binding energy of adsorbate molecules on the Pt₃₈ cluster supported on defect containing TiO₂ is expected to be stronger than on the Pt₃₈ cluster supported on defective graphene based supports, due to higher extent of upward shift of the d-band centre of the exposed facets. The enhanced binding energy of adsorbates on the Pt₃₈ cluster supported on TiO₂ supports may be detrimental to catalyst durability and activity. This can be due to strong binding of poison molecules and reaction intermediates which maybe too strongly bound on the surface such that they cannot participate in further reaction steps. Overall it might turn out that the functionalised graphene based supports are better support materials over the TiO₂ based materials for particular reactions. The Nb-doped partially reduced TiO₂(110) surface attaches the Pt₃₂Pd₆ cluster strongly to the support compared to the functionalised graphene supports. Furthermore, the binding energy of adsorbate molecules is expected to be weaker on the Pt₃₂Pd₆ cluster supported on the Nbdoped partially reduced TiO₂(110) surface compared to the functionalised graphene supports. This might be beneficial as poison molecules may be weakly bound to the cluster resulting in high resistance to poisoning which can also have a positive effect on catalyst activity. In addition to enhancing binding of the cluster to the support and affecting the binding energy of adsorbates on the supported clusters, some of the defects can also alter the ordering pattern of Pd and Pt atoms within the Pt₃₂Pd₆ cluster. OH functionalised graphene and Nbdoped partially reduced TiO₂(110) surface result in segregation of Pd towards the clustersupport interface, thereby exposing more Pt atoms at the surface facets of the cluster. The modified arrangement of Pt and Pd atoms may result in modification of the reactivity of the Pt₃₂Pd₆ cluster. The results of this study indicate that the defects can play a vital role in determining the activity and durability of the catalyst. By having the right combination of defects on the support material, the durability and catalytic activity of the catalyst can be fine-tuned simultaneously. This can lead to better design of catalysts.